2021
DOI: 10.3390/universe7010018
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering Dynamics of Primordial Black Holes in N-Body Simulations

Abstract: We explore the possibility that Dark Matter (DM) may be explained by a nonuniform background of approximately stellar mass clusters of Primordial Black Holes (PBHs) by simulating the evolution from recombination to the present with over 5000 realisations using a Newtonian N-body code. We compute the cluster rate of evaporation and extract the binary and merged sub-populations along with their parent and merger tree histories, lifetimes and formation rates, the dynamical and orbital parameter profiles, the degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…Building on prior results [29,[33][34][35] (cf. also to [36]), we have argued in Ref. [32] that PBHs form clusters at very high redshifts which evaporate later due to the continuous loss of PBHs in the high-energy tail of the Maxwell-Boltzmann energy distribution.…”
Section: Consistency Of Primordial Black Hole Dark Matter With Ligo/virgo Merger Ratesmentioning
confidence: 77%
“…Building on prior results [29,[33][34][35] (cf. also to [36]), we have argued in Ref. [32] that PBHs form clusters at very high redshifts which evaporate later due to the continuous loss of PBHs in the high-energy tail of the Maxwell-Boltzmann energy distribution.…”
Section: Consistency Of Primordial Black Hole Dark Matter With Ligo/virgo Merger Ratesmentioning
confidence: 77%
“…We expect the fraction of BH in binaries to be quite small. In some simulations of BH clusters it has been shown that f b O(10 −3 ) [25]. If we adopt this as a fiducial value, and because f BH ≤ 1 then it holds that…”
Section: A the Abundance Constraintmentioning
confidence: 97%
“…This is also a problem for clustered distributions, with the additional complication that the initial distribution could also depend on an enlarged set of parameters (given by -in principle-independent N-point correlations functions). Despite these dificulties, some interesting results have been obtained in determining the merger rate for some families of clustered distributions, with the use of numerical simulations [25,26]. For example, BBHs merging inside globular clusters can exhibit α = 2.3 +1.3 −1.0 [26].…”
Section: Introductionmentioning
confidence: 99%
“…We note that the normalization of PBH merger rate has nothing to do with the fraction of CDM as our merger rate model described in Eq. ( 7) depends on the combination R clust f tot 2 PBH , which is the known degeneracy between clustering and abundance of PBHs (Raidal et al 2017;Clesse & Garcia-Bellido 2020;Vaskonen & Veermäe 2020;Young & Byrnes 2020;Trashorras et al 2021;Atal et al 2020;De Luca et al 2020b).…”
Section: Distinguishing Between Pbhs and Abhs Using The Duty Cyclementioning
confidence: 99%